Patient perspective in obesity surgery: goals for weight loss and improvement of body shape in a prospective cohort dtudy - Nickel, Felix; Schmidt, Lukas; Tapking, Christian; Bruckner, Thomas; Müller, Beat P. (Obesity facts, 2018)
Objective: Obesity surgery provides sustainable weight loss, improvement of comorbidities, and improved quality of life (QOL). There is few evidence on the patient perspective and goals. This study compared expected and achieved weight loss, body shape, and QOL. Methods: Patients completed the Moorehead-Ardelt QOL questionnaire (MAQOL) and questionnaires on actual and expected weight loss and body shape, comorbidities, and goals of obesity surgery preoperatively and within 24 months postoperatively. Results: 44 patients completed questionnaires pre- and postoperatively. BMI, MAQOL and comorbidities significantly improved postoperatively. Patients’ expected weight loss goal corresponded to a postoperative BMI of 32.6 ± 5.6 kg/m2 and was not different from their achieved BMI within 24 months after surgery (33.9 ± 6.3 kg/m2, p = 0.276). Self-reported body shape improved but did not reach preoperatively expected goals. During the weight loss period, patients adapted their weight loss and body shape goals to higher levels. Patients attributed a higher part of their success in weight loss to surgery postoperatively (79.5 ± 22.0 vs. 89.1 ± 18.4%, p = 0.028). Conclusion: Patients lost as much weight as they had expected and later modified the goals to even greater weight loss. Body shape improved but did not reach expected levels. QOL improved independently from weight loss and body shape. Patients attributed successful weight loss predominantly to surgery.